Probiotics for the control of obesity – Its effect on weight change. Issue 1 (March 2016) - Rouxinol‐Dias, Ana Lídia; Pinto, Ana Raquel; Janeiro, Catarina; Rodrigues, Daniel; Moreira, Marta; Dias, João; Pereira, Pedro
ABSTRACT : Background: : Obesity is a growing epidemic worldwide. Evidence so far demonstrates that the bacteria that are commonly found in the human gastrointestinal tract affect nutrient acquisition and energy regulation. This suggests that an important role is played by gut microbiota in the development of obesity. Objectives: : Our main goal was to assess if a probiotic diet leads to a significant difference in weight change in non‐obese and obese people, and in experimental models. Methods: : Search was undertaken in PubMed, Scopus, ISI Web of knowledge, Cochrane Central Register of Controlled Trials, Google scholar, meta‐Register of Controlled Trials, ClinicalTrials.gov and by scanning reference lists of articles, without publication date imposed, for randomised clinical trials studying the administration of probiotics to obese or overweight patients and experimental studies in experimental models and healthy humans. Search terms included probiotics, obesity, weight, BMI, weight gain, weight loss, weight change, probiotic diet and probiotic therapy. In an unblended standardized manner, 2 reviewers analysed the searched studies, using the defined inclusion and exclusion criteria, and performed extraction of data, in an independent way, using predefined data fields. Results: : We've identified, through searching databases specified in methods, 269 records. A total of 4 clinical trials and 14 experimental studies were included in the systematic review. Among the 4 randomized clinical trials only one showed statistically significant results. L. rhamnosus CGMCC 1.3724 was efficient in reducing weight in females, but not in males ‐ Mean weight loss 12 week/24 week (kg): Males‐probiotic: 4/5.4; Males‐placebo: 3.05/4.43; Females‐probiotic: 4.4/5.2; Females‐ placebo: 2.6/2.5 (P<0.05 only on females). Conclusions: : In our systematic review, we found that probiotic effect in body weight is specie and strain specific. L. gasseri BNR17, reduced the weight gain compared to controls; L. gasseri L66‐5 promoted weight gain, L. rhamnosus GGMCC is the only one that had a positive effect in weight loss in humans. Probiotic effect in body weight was species and strain specific. On the other hand L. plantarum LG42, L. gasseri SBT2055 and L. plantarum co‐therapy with KY103 and L. curvatus HY7601 had an anti‐obesity effect in animal models.